Stress Factors and Macronutrient Intake to Total Cholesterol Levels and HDL Levels in Overweight Female Students - Damayanti, Amilia Yuni; Fathimah, Fathimah; Sari, Atika Rahma; Pibriyanti, Kartika (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Being overweight is one of the many health problems that occur in modern times. Stress and macronutrient intake are factors that can affect the occurrence of increased cholesterol levels and decreased HDL in overweight. This study aimed to determine the relationship between stress factors and macronutrient intake on cholesterol and HDL levels. This research uses a cross-sectional design with a purposive sampling method, namely selecting subjects with certain criteria. The number of subjects was 50 Overweight female students based on the population proportion sample formula calculation. Stress data was measured using the Depression, Anxiety, and Stress Scale (DASS 42) questionnaire and macronutrient intake data using a 24-hour food recall form. Data analysis using the Chi-square test. The results obtained stated that 30% of respondents had high cholesterol levels, 2% of respondents had low HDL levels. As many as 22% of respondents experienced stress, the carbohydrate intake of 80% of respondents was inadequate, the protein intake of 96% of respondents was inadequate, the fat intake of 96% of respondents was inadequate. Analysis of the relationship between stress and total cholesterol (p=0.152), carbohydrate intake (p=0.416), protein (p=0.331) fat (p=0.669) with total cholesterol levels, carbohydrate intake (p=0.080) protein (0.960) fat (0.960 ) with HDL levels. Stress factor with HDL levels (p=0.044). It can be concluded that there is no relationship between stress factors, carbohydrate, protein and fat intake with total cholesterol levels. There is no relationship between carbohydrate, protein and fat intake with HDL levels. There is a significant relationship between stress factors and HDL levels in overweight female students.